CCDC141 Mutation Identified in Anosmic Hypogonadotropic Hypogonadism (Kallmann Syndrome) Alters GnRH Neuronal Migration - Hutchins, B. Ian; Kotan, L. Damla; Taylor-Burds, Carol; Ozkan, Yusuf; Cheng, Paul J.; Gurbuz, Fatih; Wray, Susan (Oxford Univ Press Inc, 2016)
The first mutation in a gene associated with a neuronal migration disorder was identified in patients with Kallmann Syndrome, characterized by hypogonadotropic hypogonadism and anosmia. This pathophysiological association results from a defect in the development of the GnRH and the olfactory system. A recent genetic screening of Kallmann Syndrome patients revealed a novel mutation in CCDC141. Little is known about CCDC141, which encodes a coiled-coil domain containing protein. Here, we show that Ccdc141 is expressed in GnRH neurons and olfactory fibers and that knockdown of Ccdc141 reduces GnRH neuronal migration. Our findings in human patients and mouse models predict that CCDC141 takes part in embryonic migration of GnRH neurons enabling them to form a hypothalamic neuronal network to initiate pulsatile GnRH secretion and reproductive function.
Keywords: Lhrh Neurons; Cortical Interneurons; Axophilic Migration; Hormone-1 Neurons; Signaling Protein; Explant Cultures; Tuba1A Mutations; Leading Process; Gene; Schizophrenia